1998
DOI: 10.1111/1468-0297.00290
|View full text |Cite
|
Sign up to set email alerts
|

Unions and Efficient Training

Abstract: The paper examines the optimal level of training investment when trained workers are mobile, wage contracts are time‐consistent, and training comprises both specific and general skills. The firm has ex post monopsonistic power that drives trained workers' wages below the social optimum. The emergence of a trade union bargaining at the firm‐level can increase social welfare, by counterbalancing the firm's ex post monopsonistic power in wage determination. Local union‐firm wage bargaining ensures that the post‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 18 publications
4
65
0
Order By: Relevance
“…They argue that unions serve as a commitment device by overcoming the infeasibility of long-term wage contracts, since trainees are guaranteed at least the union wage in the future. Booth and Chatterji (1998) show that unions can bring the level of training closer to the social optimum by setting a sufficiently high training wage and therefore decrease turnover. Böheim and Booth (2004) and Green et al (1999) find empirical evidence that workers with union coverage received more training in Britain, whereas Booth et al (2003) find in addition that unionized workers received a higher return to training and a higher wage growth compared to workers without training.…”
Section: Relevant Literaturementioning
confidence: 98%
“…They argue that unions serve as a commitment device by overcoming the infeasibility of long-term wage contracts, since trainees are guaranteed at least the union wage in the future. Booth and Chatterji (1998) show that unions can bring the level of training closer to the social optimum by setting a sufficiently high training wage and therefore decrease turnover. Böheim and Booth (2004) and Green et al (1999) find empirical evidence that workers with union coverage received more training in Britain, whereas Booth et al (2003) find in addition that unionized workers received a higher return to training and a higher wage growth compared to workers without training.…”
Section: Relevant Literaturementioning
confidence: 98%
“…Unions may ensure that 4 In another context, Booth and Chatterji (1998) show that union-firm wage bargaining can prevent ex-post monopsonistic wage-setting by firms and can thereby reduce inefficient quits. 6 covered workers receive higher wages and greater job security by directly intervening in training provision, for example by making sure that workers' skills are deepened and/or kept up-to-date through more training.…”
Section: Union Concern Over the Wage-employment Packagementioning
confidence: 99%
“…By contrast, it has been found that unionized plants are more likely to utilize incentive payments, also accompanied by joint decision-making, that lead to better results in terms of firm performance (Black and Lynch, 2001 (Bryson and Forth, 2010). This means that in unionized firms, constructive institutional responses overcome free rider problems of group incentives, increase workers' commitment and reduce voluntary labor turnover (Booth and Chatterji, 1998). …”
mentioning
confidence: 99%